Photochemical and electrochemical catalytic reduction of CO2 with NHC-containing dicarbonyl rhenium(i) bipyridine complexes. Issue 37 (13th June 2016) - Maurin, Antoine; Ng, Chi-On; Chen, Lingjing; Lau, Tai-Chu; Robert, Marc; Ko, Chi-Chiu
Abstract : Efficient photochemical and electrochemical CO2 -to-CO conversion using the N, O and N, S -NHC-containing dicarbonyl rhenium(i ) bipyridine complexes is described. Abstract : The electrochemical and photochemical catalytic reductions of CO2 using N, O and N, S -NHC-containing dicarbonyl rhenium(i ) bipyridine complexes have been investigated. By replacing the carbonyl ligand in tricarbonyl rhenium(i ) complexes with a weaker π-accepting ligand, the characteristic MLCT transitions shifted to lower energy. This makes photocatalysts capable of harvesting low-energy visible light for catalyzing CO2 reduction. A detailed study revealed that these dicarbonyl rhenium(i ) complexes are also highly selective for photocatalysis of CO2 to CO with a good quantum efficiency (10%), similar to that of the tricarbonyl rhenium(i ) complex analogues. From the electrochemical study, it was observed that the catalysts efficiently produce CO from CO2 with high turnover frequency and good stability over time.